STANDAR RESEP LAPEK KOCI DI DESA TANJUNG SABAR KECAMATAN PARIAMAN UTARA KOTA PARIAMAN - HANI, IKHVAR; Baidar, Baidar; Gusnita, Wiwik (Journal of Home Economics and Tourism, 2016)
This study aims to find a standard recipe lapek koci, and quality lapek koci. Type of research is a mixture (Mixed Method). This research was conducted in the village of Tanjung Sabar from the date of December 10, 2015 until April 1, 2016. The data source is twofold: a source of qualitative data obtained from community experts and traders are experts at making lapek koci at Tanjung Sabar, a source of quantitative data obtained from 10 panelists from the public and limited to 5 panelists from lecturers Catering FPP-UNP. Based on the results of quantitative research organoleptic lapek koci standard recipe that has been converted with 4 repetitions found the quality of lapek koci include: a pyramid shape (t = 4,5.pxl = 4) 3.8%, 3.8% immaculate shape, color leather (dark brown) 4%, the fill color (dark brown) 4%, leather aroma (scented brown sugar) 3.8%, the content of aroma (scented green beans) 4%, skin texture (chewy) 4%, the texture of the content ( fine) 4%, skin taste (sweet) 3%, and the flavor of the contents (sweet) 3%.Keywords : standard recipe lapek koci , quality